Security in computing and communications : third international symposium, SSCC 2015, Kochi, India, August 10-13, 2015. Proceedings /: third international symposium, SSCC 2015, Kochi, India, August 10-13, 2015. Proceedings. (2015) - Unknown
No abstract available